Corporate Social Responsibility: A Literature Review On Practices, Implications, And Future Directions - Rizki Agung Santoso; Tulus Harefa; Luk Luk Fuadah (International Journal of Economics Accounting and Management, 2024)
Corporate Social Responsibility (CSR) has become an integral component of corporate governance and business strategy across various sectors. This literature review explores recent developments in Corporate Social Responsibility (CSR) and its multifaceted impact on corporate reputation, financial performance, and crisis management. CSR, once focused primarily on social and environmental initiatives, has evolved to include digital responsibility, reflecting its adaptability to modern corporate demands. The COVID-19 pandemic highlighted CSR’s critical role in fostering resilience, as companies that prioritized social contributions and public health maintained stronger market positions. Additionally, CSR influences ethical considerations in areas such as tax management and data responsibility, raising questions about its authentic application and the potential need for regulatory oversight. Through an analysis of recent studies, this review emphasizes that CSR serves as both a strategic advantage and an ethical mandate. Notably, CSR’s expansion into Corporate Digital Responsibility (CDR) highlights its relevance in addressing contemporary issues like cybersecurity and data protection. As businesses navigate evolving social and technological landscapes, CSR continues to drive value by building trust, enhancing corporate reputation, and supporting sustainable business models